KEMANDIRIAN FINANSIAL LEMBAGA PENDIDIKAN MELALUI ENTREPRENEURSHIP DAN PARTNERSHIP - Ahmad Romadhon (Jurnal Manajemen Pendidikan, 2016)
The objective of this research was to understand comprehensively the Financial Independent in Organization of Education through Entrepreneurship and partnership. it was a qualitative research with study case method conducted in Al Ashriyyah Nurul Iman Islamic Boarding School, Parung-Bogor. In this research data collecting with triangulation technique, Overall the researchers use participant observation, in-depth interviews, and documentation for the same data sources simultaneously. As a private educational institution, Al Ashriyyah Nurul Iman Foundation since its inception independently manage and develop the foundation to establish a wide range of entrepreneurial and cooperation with various institutions and circles. Financial independence has always strived through two things very well. Develop without relying on finance from other parties is a priority for YANIIBS, so that entrepreneurship and partnerships with these institutions become more developed and advanced